Efficacy of the MMP inhibitor MMI270 against lung metastasis following removal of orthotopically transplanted human colon cancer in rat. - Ogata, Y; Matono, K; Nakajima, M; Sasatomi, T; Mizobe, T; Nagase, H; Shirouzu, K (2006)
We have investigated the antitumor effects of synthetic MMP inhibitor MMI270 against postoperative lung metastasis from colon cancer in nude rat. The KM12SM human colon cancer cells were injected into the cecal wall, and at 5 weeks after the injection, the cecum was removed including the tumor. Then, 30 mg/kg of MMI270 was administered perorally twice per day for 2 or 4 weeks, either immediately after removal or after week 2 after the removal. At week 7 after the removal, lung metastasis was significantly inhibited by the early administration of MMI270 immediately after the tumor removal but not by the late administration. The survival rates were significantly higher in the rats treated by early administration of MMI270 compared to the survival rate in untreated rats. Moreover, no lung metastasis was detected in some rats with 24-weeks' survival treated by early administration. Lower microvessel density, lower PCNA Index and higher Apoptotic Index in the lung metastases of the rats treated with MMI270 were found compared to those in untreated rats. A beneficial effect of by early administration of MMI270 against postoperative lung metastases may be expected through inhibiting neovascularization of metastases in nude rat.